Fragmenting modernism Ford Madox Ford, the novel, and the Great War - Haslam, Sara (Manchester University Press, 2002)
"This is a book about Ford Madox Ford, a hero of the modernist literary revolution. As a friend and critic of Ezra Pound and Joseph Conrad, editor of the English Review, and author of The Good Soldier, he shaped the development of literary modernism. Through his grandfather, Ford Madox Brown, and his father, a German music critic, he also manifested formative links with mainland European culture and the visual arts."--BOOK JACKET.